Development of Entrepreneurship Competencies in Students from Universidad de la Amazonia (2019-2020) - Milton César Andrade-Adaime; Yelly Yamparli Pardo-Rozo; Claritza Marlés-Betancourt (I+D Revista de Investigaciones, 2022)
The Tuning study carried out in Latin America with validity for Colombia identified specific competencies for professionals in Administration, among them those related to Entrepreneurship. The objective of this study was to know the perception of Business Administration students (PAE) on the importance and development of competencies in entrepreneurship. The semi-structured survey technique was applied to a sample of 73 % of the students of the professionalization and deepening cycle. Descriptive and correlation analysis was used. In order of importance, the following capacities were determined: detection of opportunities to undertake new businesses, development of new products, analysis of information for decision making, identification and optimization of business opportunities. The average rating was 3.7 (on a scale of 1.0 to 5.0), which places the training at a medium level (scale: low, medium, high). These results were consistent with the national trend.